Comparative molecular field analysis of dopamine D4 receptor antagonists including 3-[4-(4-chlorophenyl)piperazin-1-ylmethyl]pyrazolo[1,5-a]pyridine (FAUC 113), 3-[4-(4-chlorophenyl)piperazin-1-ylmethyl]-1H-pyrrolo-[2,3-b]pyridine (L-745,870), and clozapine. - Lanig, Harald; Utz, Wolfgang; Gmeiner, Peter (Journal of Medicinal Chemistry, 2001)
A CoMFA study was undertaken to elucidate the correlation of biological activity and structural parameters of 25 dopamine D4 antagonists. A special point of interest is that we have included the atypical D4 antagonist clozapine as a structural template for all other compounds. After comparing potential protonation sites at semiempirical (AM1) and ab initio (6-31G(d)) levels of theory, possible conformations of the lead compound 3-[4-(4-chlorophenyl)piperazin-1-ylmethyl]pyrazolo[1,5-a]pyridine (FAUC 113) were investigated by systematic semiempirical conformational analysis. The final conformation of FAUC 113, which was used as a template for the other compounds in the dataset, was chosen by clustering and rigid body alignment of all conformations to clozapine. The CoMFA applied on the final alignment resulted in a q2cv of 0.739. To elucidate the influence of the absolute orientation of the molecules within the grid space, the entire dataset was systematically rotated (1296 steps) within the lattice. The Gaussian-shaped distribution of the q2cv values spanned the range of 0.699-0.794 and therefore supports the significance of the analysis.